Acute liver function decompensation in a patient with sickle cell disease managed with exchange transfusion and endoscopic retrograde cholangiography. (September 2014) - Papafragkakis, Haris; Ona, Mel A.; Changela, Kinesh; Sadanandan, Swayamprabha; Jelin, Abraham; Anand, Sury; Duddempudi, Sushil
Sickle cell intrahepatic cholestasis is a relatively uncommon complication of homozygous sickle cell anemia, which may lead to acute hepatic failure and death. Treatment is mainly supportive, but exchange transfusion is used as salvage therapy in life threatening situations. We describe a case of a 16-year-old female with homozygous sickle cell anemia who presented to the emergency room with fatigue, malaise, dark urine, lower back pain, scleral icterus and jaundice. She was found to have marked hyperbilirubinemia, which persisted after exchange transfusion. Because of the concomitant presence of gallstones and choledocholithiasis, the patient underwent endoscopic ultrasound and laparoscopic cholecystectomy followed by endoscopic retrograde cholangiography and sphincterotomy.